2022
DOI: 10.1167/iovs.63.5.37
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes, Fasting Glucose, Hemoglobin A1c Levels and Risk of Primary Open-Angle Glaucoma: A Mendelian Randomization Study

Abstract: Purpose To evaluate the potential causal associations between type 2 diabetes and fasting glucose and HbA1c levels and the risk of primary open-angle glaucoma (POAG) in European and East Asian populations. Methods We selected genetic variants ( P < 5 × 10 −8 ) for type 2 diabetes (898,130 Europeans; 433,540 East Asians), fasting glucose, and HbA1c (196,991 Europeans; 36,584 East Asians) from three meta-analyses of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
2
10
0
1
Order By: Relevance
“…Epidemiologically, numerous studies have been conducted, and the majority have shown an association between glaucoma and type 2 DM 3 , 13 , 14 . Whether this is a causal relationship, i.e., whether diabetes has a causal effect on the pathogenesis and progression of POAG, is the subject of intense scientific debate.…”
Section: Glaucoma and Diabetes – Epidemiology And Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologically, numerous studies have been conducted, and the majority have shown an association between glaucoma and type 2 DM 3 , 13 , 14 . Whether this is a causal relationship, i.e., whether diabetes has a causal effect on the pathogenesis and progression of POAG, is the subject of intense scientific debate.…”
Section: Glaucoma and Diabetes – Epidemiology And Possible Mechanismsmentioning
confidence: 99%
“…Epidemiologisch existieren zahlreiche Untersuchungen, die in der Mehrzahl einen Zusammenhang zwischen Diabetes mellitus Typ 2 und Glaukom gezeigt haben 3 , 13 , 14 . Ob es sich hier um einen kausalen Zusammenhang handelt, d. h. der Diabetes die Entstehung und Progression des POWG ursächlich beeinflusst, ist Gegenstand intensiver wissenschaftlicher Diskussionen.…”
Section: Glaukom Und Diabetes – Epidemiologie Und Mögliche Mechanismenunclassified
“…Besides, MR studies avoids reverse causality because of the genetic variant used as IVs were generated earlier than most of outcomes happening ( Hingorani and Humphries, 2005 ). Recent MR studies have demonstrated that type 2 diabetes ( Hu et al, 2022 ), myopic refractive error ( Choquet et al, 2022 ), coffee consumption ( Li et al, 2022 ), and blood lipid-related metabolites ( Nusinovici et al, 2022 ) have potential causal associations with glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the use of MR approaches in the context of POAG has been relatively limited. Despite this, these methods have been successfully implemented to explore the relationship between POAG and a small number of traits including brain alterations 11 , plasma lipid levels 12 , fatty acids 13 , type 2 diabetes 14 , HbA1c levels 14 , fasting glucose, coffee consumption 15 and blood pressure 16 .…”
Section: Introductionmentioning
confidence: 99%